Mutations in BRCA1 and BRCA2 Generate Distinct Ovarian Tumour Microenvironments and Differential Responses to Therapy - Farokhi Boroujeni, Salar (Université d'Ottawa / University of Ottawa, 2023)
Clinical trials are currently exploring the combinations of P ARP inhibitors and immunotherapies in the treatment of ovarian cancer, but their effects on the ovarian tumour microenvironment (TME) remain unclear. Here, we investigate how olaparib, PD-L1 monoclonal antibodies and their combination can influence TME composition and survival of tumour-bearing mice. We further explored how BRCA mutations can influence the response to therapy. Olaparib and combination therapies similarly improved the median survival of Brca1- and Brca2-deficient tumour-bearing mice. Anti-PD-L1 monotherapy improved the survival of mice with Brca1-null tumours, but not Brca2-null tumours. A detailed analysis of the TME revealed that the olaparib monotherapy resulted in a large number of immunosuppressive and immunomodulatory effects in the more inflamed Brca1-deficient TME but not Brca2-deficient tumours. Anti-PD-L1 treatment was mostly immunosuppressive, resulting in a systemic reduction of cytokines and a compensatory increase of PD-L1. The results of the combination therapy generally resembled the effects of one or both of the monotherapies, along with unique changes observed in certain immune populations. In-silico analysis of RNA-seq also revealed numerous differences between Brca-mutated tumour models. In summary, these findings shed light on the influence of novel therapeutics and BRCA mutations on the ovarian TME.
Keywords: PARP; TME; BRCA1; BRCA2; Olaparib; PD-L1